PERSISTENCE AND ACADEMIC ACHIEVEMENT IN FOREIGN LANGUAGE IN NATURAL SCIENCES STUDENTS - Alexandr I Krupnov; Yulia V Kozhukhova; Alexandra A Vorobyeva (Peoples' Friendship University of Russia (RUDN University), 2017)
The article discusses the results of empirical study of the association between variables of persistence and academic achievement in foreign languages. The sample includes students of the Faculty of Physics, Mathematics and Natural Science at the RUDN University ( n = 115), divided into 5 subsamples, two of which are featured in the present study (the most and the least successful students subsamples). Persistence as a personality trait is studied within A.I. Krupnov's system-functional approach. A.I. Krupnov's paper-and-pencil test was used to measure persistence variables. Academic achievement was measured according to the four parameters: Phonetics, Grammar, Speaking and Political vocabulary based on the grades students received during the academic year. The analysis revealed that persistence displays different associations with academic achievement variables in more and less successful students subsamples, the general prominence of this trait is more important for unsuccessful students. Phonetics is the academic achievement variable most associated with persistence due to its nature, a skill one can acquire through hard work and practice which is the definition of persistence. Grammar as an academic achievement variable is not associated with persistence and probably relates to other factors. Unsuccessful students may have difficulties in separating various aspects of language acquisition from each other which should be taken into consideration by the teachers.